DETERMINANT DEBT POLICY (STUDY IN MANUFACTURING COMPANY SUBSECTORS FOOD AND DRINK LIST IN INDONESIAN STOCK EXCHANGE) - Denok Pratiwi; Isti Fadah; Nurhayati Nurhayati; Yustri Baihaqi (UPT Penerbitan Universitas Jember)
The purpose of this research is to analyze the influence of institutional ownership, managerial ownership, Profit Margin on Sales, Return On Equity and Basic Earning Power on debt policy. The sampling technique utilized in this research is purposive sampling. There are 10 manufacturing companies in food and beverages sub sector which listed in Indonesia Stock Exchange period 2012-2016 taken as the samples of this research . Data analysis technique that used is multiple linear regression analysis. The results of statistical tests show that institutional ownership, Profit Margin on Sales and Basic Earning Power have a negative and significant effect on debt policy. Return On Equity has a positive and significant effect on debt policy. Managerial ownership has a positive and insignificant effect on debt policy.